Caracterização fenotípica de Leishmania infantum obtidas de pacientes refratários ao tratamento com antimonial - Magalhães, Lucas Sousa (2016)
Visceral leishmaniasis (VL) is a serious infectious disease that if left untreated can lead to death. Chemotherapy is the main form of treatment and antimony are the drugs of first choice. Treatment efficacy is a consequence of the immunological profile of the patient, the pharmacokinetic properties of the drug and the inherent differences in each strain. The resistance of parasites to the antimonial and resistance to treatment is emerging worldwide. Few studies using clinical isolates of patients refractory to treatment seeking to understand the machinery of resistance. Thus, the present study aimed to characterize phenotypic components of clinical isolates of Leishmania (L.) infantum obtained from patients with LV refractory to treatment with Glucantime®. changes were evaluated ultrastructural front of the trivalent antimony (SbIII) and Action transport pumps related to drug efflux. In total, four strains were used: Two isolates treatment refractory patients and two isolates from patients responsive to treatment with antimony. The susceptibility of these strains was evaluated in vitro exposure to increasing concentrations of promastigotes SbIII and determination of median inhibitory concentration (IC50). In comparison, the IC50s of separate refractory patients are significantly greater than the IC50 of patients responsive isolated, showing an in vitro drug resistance profile. From these results, the concentration of 615 μM of SbIII was chosen to perform the experiments. This concentration proved to be toxic, but fully compatible with survival in all isolates. Then the isolates were subjected to transmission electron microscopy (TEM) after being exposed to 615 μM of SbIII for 48 hours. The two isolates from patients responsive to treatment demonstrated significant ultrastructural changes, with the presence of vacuolization, disorganization and cytoplasmic compression with increased eletrodensidade, and the strong presence of cells with intense loss eletrodense the cytoplasm, indicating incompatibility with life. While the two isolates from treatment refractory patients had preserved ultrastructure, with the presence of morphologically altered, compressed and electrodense cells, indicating the stress response. Finally, to assess the presence of transmembrane transport mechanisms related to drug efflux, the isolates were subjected to two protocols: using the fluorescent probe Rhodamine 123 with the channel blocker, verapamil hydrochloride, and the exposure to SbIII plus verapamil hydrochloride The results showed that MDR-1 type pumps are not related to the different in vitro resistance profiles to antimony in isolates from antimony-refractory patients. Together, the results of this study show that clinical refractory patients isolates have phenotypic characteristics that make her different behavior of isolates from patients responsive when exposed to antimony in vitro.